Patients With Lower Eyelid Orbital Fat Hyperplasia. Issue 7 (October 2015) - Baek, Ji Sun; Jang, Jae Woo
Abstract : Purpose: Lower eyelid orbital fat hyperplasia has not been described in young age patients. Methods: A fourteen-year-old girl, a 29-year-old man, and 42-year-old man had visited our hospital complaining of a lower eyelid bulge. In orbital computed tomography examination, there was excess fat tissue compared with the opposite side, but no mass lesion matched with the area of lower eyelid bulge in our patients. The authors planned surgery for the removal of excess fat through the conjunctival incision. Intraoperatively, there was no real fat herniation through the septum. Septum continuity was maintained and thinning or distention of the orbital septum was not observed in our patients. The authors opened the orbital septum and removed the excess fat to make symmetry bilaterally. In the pathologic examination, removed fat tissue is not different with normal fat tissue. Conclusions: The authors reported these findings at the first time. So they proposed the patient's condition as "lower eyelid orbital fat hyperplasia."